2006
DOI: 10.1111/j.1524-4725.2006.32169.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Digital Image Management Software for Improved Patient Care and Optimal Practice Management

Abstract: A variety of computer applications are available to optimize the use of digital images in the dermatologic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Pre-treatment and post-treatment evaluation, documentation and skin care Recommendation 3: We recommend a clinical and digital photographic evaluation and documentation to be completed in conjunction with the laser/IPL procedures (GRADE 1C). 30,33,34 We recommend against avoidance of laser treatment in patients who are on or have recently stopped using oral isotretinoin (GRADE 2C). [35][36][37]…”
Section: Qualification Of Providers Of Laser And/or Ipl Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treatment and post-treatment evaluation, documentation and skin care Recommendation 3: We recommend a clinical and digital photographic evaluation and documentation to be completed in conjunction with the laser/IPL procedures (GRADE 1C). 30,33,34 We recommend against avoidance of laser treatment in patients who are on or have recently stopped using oral isotretinoin (GRADE 2C). [35][36][37]…”
Section: Qualification Of Providers Of Laser And/or Ipl Treatmentmentioning
confidence: 99%
“…6 Recent clinical studies showed that invasive acne scar treatments and laser procedures in patients on oral isotretinoin bring no additional risks and that the drug does not delay wound healing. [35][36][37] Disease-related measurements and reporting standards 30,34 Recommendation 4: We recommend the use of clinical (depending on the disorder treated) and photographic outcome measurements to evaluate the primary outcome of laser/IPL procedures (GRADE 1A).…”
Section: Medical History and Clinical Examinationmentioning
confidence: 99%
“…Psychiatrists also worry that patients may adjust what they discuss during psychiatric visits based on the perceived privacy of the record [41]. Ophthalmology and dermatology both have high patient volume, require the integration of specialized images and hand written drawings, and typically include both a busy outpatient practice and surgical procedures [13,19,22,44]. Pediatricians have many specific information needs that differ from those of physicians who care for adults, including immunization management, documentation of growth, and weight and age based dosing [43].…”
Section: Potential Explanations For Ehr Adoption Variability Among Phmentioning
confidence: 99%
“…11 The ability to track disease progression and search image databases by patient age, sex, location of image, disease process, procedure, and date would be particularly helpful. [19][20][21][22] While this is currently the rare exception, an EMR system is maximally effective when the entire health care system shares information. Optimally, new laboratory values, radiology reports, dermatopathology reports, and consultations from other physicians are flagged for daily review and then automatically inserted into the EHR.…”
Section: Effect On Quality Of Carementioning
confidence: 99%